The Development of Tourism Village Business Model (Case in Tourism Village of Kampung Bambu Banyuresmi) - Diqbal Satyanegara; Muhammad Johan Widikusyanto (International Journal of Business Studies, 2023)
During Covid 19 pandemic, tourism village requires appropriate business model to sustain and survive in order to achieving organization goals. One of the adaptable business models is Business Model Canvas which able to convert complexity of business model into simplify and easy to understand. This research is trying to identify and map current business model of Desa Wisata Kampung Bambu, evaluate business model by SWOT analysis, formulate strategy for developing Desa Wisata Kampung Bambu, and creates design of Desa Wisata Kampung Bambu’s Business Model Canvas. 6 respondents determined intentionally with purposive sampling method consist of 5 managers representative and 1 academician. There are four elements of Business Model Canvas chosen to be prioritize by Desa Wisata Kampung Bambu in order to revise their business strategy among others : Key Activites, Value Proposition, Cost Structure, dan Revenue Streams. Business Model Canvas result also reveals that Desa Wisata Kampung Bambu should make improvements to the model business along with strategy for business development in the future. As consequences, this would be impact to spending activity, potential revenue, primary activity, and Desa Wisata Kampung Bambu’s value proposition.